Central Bank Digital Currencies for Cross-border Payments : A Review of Current Experiments and Ideas - World Bank (World Bank, Washington, DC, 2021)
Over the years, the demand for seamless and inexpensive cross-border payments has grown in parallel with growth in international e-commerce, remittances and tourism. Yet, cross-border payments have not kept pace with the intensive modernization that has characterized domestic payment services worldwide. An alternative avenue to modernize delivery of cross-border payment services is being increasingly explored in the context of central banks issuing their own digital currency. A central bank digital currency (CBDC) could well incorporate options and features specifically designed to execute cross-border payments, with a view to reducing the inefficiencies and rents discussed above by shortening the payments value chain. This report discusses the use of CBDCs for cross-border payments. The report reviews the models that have been developed for this purpose to date and discusses critical legal issues that arise in the context of cross-border use of CBDC. This report is organized as follows. Section II specifically discusses the models developed jointly by the Bank of Canada, Bank of England, and Monetary Authority of Singapore; Section III evaluates how cross-border CBDCs address challenges of the existing correspondent banking arrangement; Section IV discusses the legal issues involved in cross-border use of CBDCs, and Section V concludes the report with some general remarks.